Clinical and angiographic outcome after conventional angioplasty with optional stent implantation compared with direct stenting without predilatation. Issue 6 (1st December 2002) - Miketic, S; Carlsson, J; Tebbe, U
Abstract : Objective: To compare in a randomised trial the procedural and clinical outcome and long term patency of conventional angioplasty with optional stent implantation versus direct stenting without predilatation. Methods: Patients undergoing coronary intervention for symptomatic coronary artery disease were randomly assigned to conventional angioplasty with optional stenting or to direct stent implantation without predilatation. The post-stent treatment consisted of antiplatelets. Follow up angiography was performed six months after the initial procedure. Results: Between December 1998 and August 1999, 181 of 190 eligible patients were randomly assigned to either optional stenting (n = 92) or direct stenting (n = 89). The procedural success was similar in both groups (87 (97.8%) in the optional v 87 (94.6%) in direct stenting group, p = 0.88). There were five cases of crossover from the direct stenting to the optional stenting group. Six patients experienced a Q wave myocardial infarction without further complications (4 in the optional v 2 in the direct stenting group, p = 0.36). One patient in whom coronary angioplasty failed underwent elective bypass surgery. No patients required urgent bypass surgery and no patients died. The reduction in late luminal loss (mean (SD) 1.19 (0.87) mm in the optional v 0.62 (0.69) mm in the direct stenting group, p = 0.004) led to a significant improvement in minimal luminal diameter at follow up (1.87 (0.93) mm in the optional v 2.56 (0.86) mm in the direct stenting group, p = 0.002), resulting in a significant reduction in restenosis rate, defined as > 50% diameter stenosis at follow up 6.5 (2.1) months after the initial procedure (28 (30.4%) in the optional v 14 (15.7%) in the direct stenting group, p = 0.019). Direct stenting significantly reduced the overall procedure and fluoroscopy times, the amount of contrast medium used, and the number of angioplasty catheters needed. The incidence of clinical events during the six month follow up did not differ significantly between the groups. No patient died during follow up. Conclusions: Direct stent implantation without predilatation significantly reduced late luminal loss, giving a better improvement in minimal luminal diameter and restenosis rate than with optional stenting. There were five patients in whom direct stenting failed who needed predilatation followed by stent implantation. However, in most patients direct stent implantation without predilatation is a feasible treatment option with a favourable long term outcome and a low incidence of complication. The procedure may help to reduce the cost of coronary interventions by reducing overall procedure and fluoroscopy times, the amount of contrast medium used, and the number of angiography catheters needed.